Investigation on the thermal stability and thermal behaviour of PEO(ENR-25) LiClO4 blends / Siti Rahmah Ramlan - Ramlan, Siti Rahmah (2010)
Thermal behaviour of poly(ethelyle oxide) (PEO), a semicrystalline polymer and an amorphous epoxidized natural rubber with 25 mol % epoxidation level (ENR- 25) doped with lithium perchlorate (LiClO4) at salt concentration (Y) = 0.02, 0.05, 0.07, 0.10, 0.12, 0.15 and 0.20 were studied by differential scanning calometry (DSC). Two glass transition temperatures (Tg), corresponding to the neat constituents were observed. It shows the immiscibility of the two constituents in the blends. Melting temperature (Tm) and equivalently the rate of crystallization of the blend decrease with increasing amount of salt. The slowing down of the rate of crystallization is greater for neat PEO and for blends with higher PEO content, thus, conforming the higher solvating power of PEO towards the Li salt as compared to ENR-25.